(untitled) (Biological Sciences - PJSIR, 1999)
The conventional method of broadcast and incorporation of P fertilizer was compared and evaluated with "fertigation" technology using the phosphatic source SSP and DAP at 22 and 44 kg P ha’ rate of application. Grain yield and total P uptake by Pak-Sl wheat was found to be similar irrespective of source, but rate and method of application affected them differently. Applying P by fertigation resulted in improved P fertilizer efficiency as well as agronomic effi- ciency compared to its broadcast application at sowing. Application of half ofP rate by fertigation produced grain yield and total P uptake equivalent to that obtained by full P rate applied by the conventional method indicating the possibility of substantial saving in P fertilizer input Thus for optimum yield and increased efficiency, fertigation technology could be economically used for both P fertilizer sources.